The Mental Image of the Private Banking Sector Among Customers: A Survey Study on the Audience of Al-Taif Islamic Bank in Baghdad - Muhsin, Muna Hameed (ALBAHITH ALALAMI, 2024)
This study aims to explore the mental image of Al-Taif Islamic Bank among customers in Baghdad, investigating whether this image is positive or negative. The image significantly influences the audience’s motivation for effective engagement with the bank. The researcher employed a survey methodology by designing a measurement tool and distributing it to a purposive sample of 400 respondents representing various districts of Baghdad who are customers of Al-Taif Islamic Bank. The study revealed several key findings: The overall image held by customers is well-defined and overwhelmingly positive. Customers choose the bank mainly for its attractive returns, widespread availability, and excellent reputation. The bank maintains strict confidentiality and privacy for its clients, fostering loyalty and trust. Its programs and services are risk-free, and its employees possess high competency and persuasive negotiation skills. The bank actively conducts media campaigns to promote its programs and services and ensures clients are kept informed about its financial activities and offerings. Information dissemination is handled by the bank’s Risk Management Department, social media channels, and customers’ personal experiences, which serve as a significant source of information about the bank.